Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Efektivitas Tim Pengajar di SMKN Taman Fajar - Muhammad Jamil (Jurnal Pendidikan Penggerak, 2023)
This research aims to investigate the crucial role of school principal leadership in increasing the effectiveness of the teaching team at Taman Fajar Vocational High School (SMKN). Through a qualitative approach, this research explores the leadership strategies and practices implemented by school principals to strengthen the collaboration and productivity of teaching teams in this educational environment. Research methods include in-depth interviews with school principals, teachers, as well as direct observation of the dynamics of teachers' work. Data analysis was carried out using a thematic approach to identify patterns and trends in the leadership roles carried out by school principals. The research results show that the principal's leadership plays a central role in creating a work climate that is conducive to team collaboration. Using a transformational approach, the principal at SMKN Taman Fajar encourages open communication, provides support, and empowers teaching team members to innovate in teaching methods. In addition, school principals also play a role in facilitating relevant training and professional development for the teaching team.